Mental Health and Health-Related Quality of Life of Children and Youth during the First Year of the COVID-19 Pandemic: Results from a Cross-Sectional Survey in Saskatchewan, Canada - Nazeem Muhajarine; Vaidehi Pisolkar; Tamara Hinz; Daniel A. Adeyinka; Jessica McCutcheon; Mariam Alaverdashvili; Senthil Damodharan; Isabelle Dena; Christa Jurgens; Victoria Taras; Kathryn Green; Natalie Kallio; et al. (MDPI AG, 2023)
For children and youth, the COVID-19 pandemic surfaced at a critical time in their development. Children have experienced extended disruptions to routines including in-person schooling, physical activities, and social interactions-things that bring meaning and structure to their daily lives. We estimated the prevalence of anxiety and depression symptoms of children and youth and their experiences of health-related quality of life (HRQoL), during the first year of the pandemic, and identified factors related to these outcomes. Further, we examined these effects among ethnocultural minority families. We conducted an online survey (March-July 2021) with 510 children and youth aged 8-18 years and their parents/caregivers. The sample was representative of the targeted population. We modelled the relationship between anxiety, depression (measured using the Revised Child Anxiety and Depression Scale), HRQoL (measured using KIDSCREEN-10), and sociodemographic, behavioural, and COVID-19-contributing factors using binary logistic regression. A priori-selected moderating effects of sociodemographic characteristics and self-identified ethnocultural minority groups on the outcomes were tested. The point-in-time prevalence of medium-to-high anxiety symptoms and depression symptoms was 10.19% and 9.26%, respectively. Almost half (49.15%) reported low-to-moderate HRQoL. Children reporting medium-to-high anxiety symptoms, depression symptoms, and low-to-moderate HRQoL were more likely to be aged 8-11 years, 16-18 years, ethnocultural minority participants, living in rural/urban areas, having good/fair MH before COVID-19, experiencing household conflicts, having less physical activity, and having ≥3 h of recreational screen time. Those who had more people living at home and ≥8 h of sleep reported low anxiety and depression symptoms. Ethnocultural minority 16-18-year-olds were more likely to report low-to-moderate HRQoL, compared to 12-15-year-olds. Additionally, 8-11-year-olds, 16-18-year-olds with immigrant parents, and 16-18-year-olds with Canadian-born parents were more likely to report low-moderate HRQoL, compared to 12-15-year-olds. Children and youth MH and HRQoL were impacted during the pandemic. Adverse MH outcomes were evident among ethnocultural minority families. Our results reveal the need to prioritize children's MH and to build equity-driven, targeted interventions.